SIKAP MASYARAKAT TERHADAP AKTIFITAS PENAMBANGAN EMAS TANPA IZIN DI SEKITAR KAWASAN HUTAN PEMATANG GADUNG KECAMATAN MATAN HILIR SELATAN KABUPATEN KETAPANG - darwin, .; zainal, sofyan; herawatiningsih, ratna (JURNAL HUTAN LESTARI, 2016)
Illegal gold mining activities in Pematang Gadung Village have affected the environment such as destruction of forests, pollution of watersheds and threatening the existence of animals. This research aims to analyze the attitudes of the community and the relationship between factors that affect the attitude of the community regarding the activities of illegal gold mining in Pematang Gadung Village.The method used in this research was the descriptive method and the sampling technique or interview with respondents was conducted trough purposive sampling. The number of respondents in this research was 87 respondents. The results showed that 46 (52.87%) of the respondents had a neutral attitude, 27 (31.03%) had a negative attitude (rejecting) and 14 (16.09%) had a positive attitude (accepting). The level of perception had an effect on people's attitude, while the levels of knowledge, cosmopolitan and forestry outreach had no relationship with the peopleâ€™s attitude toward illegal gold mining activities.Â Keywords: attitude, community, illegal mining, respondents, sample.